Comparison of generic and disease‐specific measures in their ability to detect differences in pressure ulcer clinical groups. Issue 4 (30th March 2019) - Rutherford, Claudia; Campbell, Rachel; Brown, Julia M.; Smith, Isabelle; Costa, Daniel S. J.; McGinnis, Elizabeth; Wilson, Lyn; Gilberts, Rachael; Brown, Sarah; Coleman, Susanne; Collier, Howard; Nixon, Jane E.
ABSTRACT: Patient‐reported outcomes can be included as end points in pressure ulcer (PU) intervention trials to provide information to inform decision‐making and improve the lives of patients. However, the challenge for researchers and clinicians is identifying and choosing an appropriate instrument for each particular application that suits their research questions and clinical context. To provide researchers and clinicians with the information needed to inform choice of patient‐reported outcome measures, we compared a generic and disease‐specific measures' ability to discriminate between clinical groups known to differ, and determined their responsiveness to change. We performed analyses on a subset of patients recruited to the PRESSURE 2 trial that completed the pressure ulcer quality of life instrument—prevention version (PU‐QOL‐P) and Short Form 12 Questionnaire (SF12) measures at baseline and 30‐day posttreatment. Known‐group validity and responsiveness‐to‐change analyses were conducted. The analysis sample consisted of 617 patients that completed both measures at baseline. Known‐group validity revealed that some PU‐QOL‐P symptoms and function scales differentiated between people with category 2 PUs and those without PUs. A less meaningful pattern of results was observed for the SF12 scales, suggesting that the PU‐QOL‐P is more sensitive to differences between PU and non‐PU populations. Responsiveness analysis revealed that the PU‐QOL‐P was more responsive in detecting disease severity than the SF12. The PU‐QOL‐P provides a standardized method for assessing PU‐specific symptoms and functioning outcomes and is suitable for quantifying the benefits of PU interventions from the patient's perspective. Generic measures are useful for group comparisons of global quality of life domains. Choice of measure for each particular application should be determined by the purpose of the measurement and the information required.